Contribuer à un projet d’aménagement par l’analyse ergonomique du travail : le cas d’une bibliothèque publique - Marie Bellemare; Sylvie Montreuil; Louis Trudel; Micheline Marier; Marie-Josée Godin; Élise Ledoux; Marie Laberge; Patrick Vincent (Perspectives Interdisciplinaires sur le Travail et la Santé)
Ergonomic considerations are increasingly being factored into work situation design, in both industrial and architectural projects. In the latter case, by participating in the definition of spaces, ergonomists also have an impact, in part, on future work organisation. Ergonomic researchers accompanied the construction of a new library in the architectural competition, design study and preliminary study phases. Basing themselves primarily on the ergonomic work analysis of the existing library and reference sites, the ergonomists analyzed the architectural proposals and then developed, with a working group, suggestions for modifying the future work framework. This article discusses the intervention activities implemented by the ergonomists during their intervention, namely ergonomic work analysis, and how the intervention was able to affect the work space and work organization. The design trajectory of two of the new library’s three floors will illustrate this and lead to a discussion of the scope and limitations of the accompanying ergonomic intervention and the conditions necessary for a positive outcome for future work.